DISTRIBUTION AND EMPOWERMENT OF ZAKAT IN MAQASID SHARIA PERSPECTIVE (Case Study of Dompet Dhuafa Waspada) - Juliana Nasution (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Distribution becomes a key issue in the management of zakat in terms of its elementary role to achieve maqasid sharia as the goal. Today, there are a plenty of innovative programs made by zakat management agencies in distributing zakat such as by DDW in North Sumatra to persuade people to give up their zakat to optimize in targeting the maqasid sharia. This study will elaborate the role of distribution in meeting the requirement of targeted maqashid sharia involving qualitative data collection method based on interview and documentary inter-rater reliability procedure. The study reveals that the distribution organized by DDW has been successfully allocating zakat to major eligible beneficiaries which are predominantly poor and not riqab. Those programs have met the indicators of the fulfillment of the maqashid sharia. This study could explore more extensively on targeting to riqab and to the supporting programs purposing to hifz an-nasl (preserving the descendants).